Data from: Two decades of altered snow cover does not affect soil microbial ability to catabolize carbon compounds in an oceanic alpine heath - Wubs, E. R. Jasper; Woodin, Sarah J.; Stutter, Marc I.; Wipf, Sonja; Sommerkorn, Martin; Van der Wal, René; Wubs, E.R. Jasper (Zenodo, 2019)
Snow strongly affects ecosystem functioning in alpine environments with potential carry-over effects outside of snow periods. However, it is unclear whether changes in snow cover affect microbial community functioning in summer. In a field experiment, we tested whether manipulation of snow cover affected the functional capabilities of the microbial community either directly, or indirectly through concomitant changes in the vegetation. While 23 years of differential snow depth and persistence fundamentally changed the vegetation composition, the microbial community's ability to catabolize a range of carbon compounds was not altered. Instead, soil moisture content was the key driver of carbon catabolism by the microbial community. Glas Maol microresp data 2009 This file contains the measured SIR rates of the microresp analysis on all of the experimental field plots. Glas Maol microresp 2009.xlsx Glas Maol vegetation survey 2009 File contains the data from the vegetation survey on all the experimental plots. Glas Maol vegetation 2009.xlsx